Isolation of ‘Candidatus Nitrosocosmicus franklandus’, a novel ureolytic soil archaeal ammonia oxidiser with tolerance to high ammonia concentration - Lehtovirta-Morley, Laura E. (FEMS Microbiol Ecol, 2016)
Studies of the distribution of ammonia oxidising archaea (AOA) and bacteria (AOB) suggest distinct ecological niches characterised by ammonia concentration and pH, arising through differences in substrate affinity and ammonia tolerance. AOA form five distinct phylogenetic clades, one of which, the ‘Nitrososphaera sister cluster’, has no cultivated isolate. A representative of this cluster, named ‘Candidatus Nitrosocosmicus franklandus’, was isolated from a pH 7.5 arable soil and we propose a new cluster name: ‘Nitrosocosmicus’. While phylogenetic analysis of amoA genes indicates its association with the Nitrososphaera sister cluster, analysis of 16S rRNA genes provided no support for a relative branching that is consistent with a ‘sister cluster’, indicating placement within a lineage of the order Nitrososphaerales. ‘Ca. N. franklandus’ is capable of ureolytic growth and its tolerances to nitrite and ammonia are higher than in other AOA and similar to those of typical soil AOB. Similarity of other growth characteristics of ‘Ca. N. franklandus’ with those of typical soil AOB isolates reduces support for niche differentiation between soil AOA and AOB and suggests that AOA have a wider physiological diversity than previously suspected. In particular, the high ammonia tolerance of ‘Ca. N. franklandus’ suggests potential contributions to nitrification in fertilised soils.